Role of adiponectin and its receptors AdipoR1/2 in inflammatory bowel disease - Qiuyan Zhu; Xiaoli Jia; Shupeng Li; Jinxing Feng (Cell Communication and Signaling)
Abstract Intake of nutrients and water from diet to maintain life, a typical physiological function of gut, is highly dependent on the extensive immune network, whose imbalance is easy to induce inflammatory bowel disease (IBD) including Crohn’s disease (CD) and ulcerative colitis (UC). Clinical strategies to completely cure IBD are poor, so it is urgent to develop novel drugs or targets. Adiponectin (APN), an adipokine from adipocytes, regulates energy metabolism and immune response. High levels APN are inversely associated with CD severity UC colonic fibrosis. However, the mechanism by which APN interferes with IBD remains unclear. This review aims to analyze correlation and molecular mechanism between APN and IBD. APN and AdipoR2 proteins are highly expressed in colon which is a primary organ of IBD, and the target intersection of APN and IBD is huge. APN may interfere with lipid metabolism in IBD individuals through AdipoR1/2, but regulates neural and peripheral immune by AdipoR1 but not AdipoR2 and mediates nutritional and energy homeostasis through AdipoR2 rather than AdipoR1. Besides, APN mediates CRP and IL-6 through AdipoR1/2, AMPK and TNF-α through AdipoR1 and PI3K-Akt, PPARA and PPARG through AdipoR2 to affect IBD progression, which depends on direct interaction between APPL1 and AdipoR1/2. Unexpectedly, AMPK and TNF-α may also interact directly with AdipoR1. APN regulates CD through AdipoR1/2-metabolism process and UC through AdipoR1-inflammation axis or AdipoR2-fibrosis process. APN analogues or AdipoRon which is a dual agonist of AdipoR1/2 potentially reduces colonic fibrosis in UC and fistulae in CD, promotes mucosal healing, repairs intestinal microbiota homeostasis and increases autophagy to alleviate IBD symptoms by weakening TNF-α, IL-6, NLRP3, TGFB1 activities and aggrandizing P-AKT, PPARA, PPARG, INS, IRS1/2, IGF-1, TIMP1, NOD2, SIRT1 levels. Graphic Abstract